2015
DOI: 10.1016/j.ultrasmedbio.2014.08.018
|View full text |Cite|
|
Sign up to set email alerts
|

Shaken and Stirred: Mechanisms of Ultrasound-Enhanced Thrombolysis

Abstract: The use of ultrasound and microbubbles as an effective adjuvant to thrombolytics has been demonstrated in vitro, ex vivo, and in vivo. However, the specific mechanisms of ultrasound-enhanced thrombolysis (UET) have yet to be elucidated. We present visual observations illustrating two mechanisms of UET: acoustic cavitation and radiation force. An in vitro flow model was developed to observe human whole blood clots exposed to human fresh-frozen plasma, rt-PA (0, 0.32, 1.58, or 3.15 μg/mL), and the ultrasound con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
193
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(202 citation statements)
references
References 63 publications
6
193
3
Order By: Relevance
“…A wide range of particle concentrations has been reported in literature for studies on sonothrombolysis. Our group has demonstrated thrombolysis in vitro for approximately 1 × 10 6 microbubbles/ml (Bader et al 2015a, b), two orders of magnitude lower than the liposome concentration achieved in this work. Shih et al have reported microbubble generation rates as high as 3 × 10 6 per s (Shih et al 2013).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…A wide range of particle concentrations has been reported in literature for studies on sonothrombolysis. Our group has demonstrated thrombolysis in vitro for approximately 1 × 10 6 microbubbles/ml (Bader et al 2015a, b), two orders of magnitude lower than the liposome concentration achieved in this work. Shih et al have reported microbubble generation rates as high as 3 × 10 6 per s (Shih et al 2013).…”
Section: Discussioncontrasting
confidence: 53%
“…However, microbubbles larger 7 µm are filtered by the lungs and thus for cavitation nucleation for enhancement of rt-PA thrombolysis. Resonant bubbles of 20–50 µm could be formed by coalescence of smaller bubbles liberated from µtELIP experiencing Bjerkness forces (Bader et al 2015a, b). Therefore, µtELIP could be tested for sonothrombolysis at sub-megahertz frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frenkel et al (2006), using both an in-vitro clot model and a numerical model to calculate clot displacement, found a correlation between thrombolytic efficacy and acoustic radiation force at 1 MHz. Bader et al (2015) found a correlation between the root-mean-square velocity of displaced in-vitro human whole blood clots and the lytic rate with sub-megahertz insonation. Radiation force is known to act on bubbles (Leighton 1994), and several groups have shown microbubbles forced into clots in-vitro (Caskey et al 2009; Acconcia et al 2013; Everbach and Guarini 2013) (Fig.…”
Section: 2 Mechanisms Of Thrombolytic Enhancementmentioning
confidence: 90%
“…Conversely, control MBs or ACPP-MBs, in the presence of thrombin-inhibiting hirudin, should have a lower binding to the clot, limited to the nonspecific adhesion of MBs. 50 Since the clot and transducer are mechanically fixed, images are perfectly coregistered throughout the experiment. We subtracted the baseline US images acquired before MB infusion from the images acquired after the final saline wash, and the signal on a pixel-by-pixel basis was converted to a color-coded heat map and overlaid on the baseline grayscale B-mode images (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%